Analisis pengaruh beban kerja, lingkungan kerja dan kepuasan kerja terhadap turnover intentions - Astutik, Yesi Puji; Liana, Lie (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to analyze the effect of workload, work environment and job satisfaction on turnover intentions. Population in this study is a contract employee who works at PT. Agility International consists of 71 members. Jenis research this is explanatory research. Methods data collection using survey with instruments in the form of questionnaires distributed to respondents. Multiple regression analysis methos is used to explain the influence between variables. The collected data were analyzed using factor analysis to testthe validity of each question item, and reliability test using cronbach alpha. Results hypothesis testing shows that the workload of positive and significant effect on turnover intentions employees, the work environment affectsh negative and significant turnover intentions employees as well as job satisfaction negative and significant effect on turnover intentions employees.